Problem-based learning: application and possibilities in Brazil - Coelho-Filho, João Macedo; Soares, Sílvia Mamede Studart; Sá, Henrique Luis do Carmo e (São Paulo Medical Journal, 1998)
The Ministry of Health launched the Family Health Program (FHP) with the aim of establishing comprehensive primary care for families and communities. The Public Health School of Ceará has been applying problem-based learning as the instructional method for the training of the family health teams. The importance of this method and the possibility of applying it in the implementation of a new and effective approach to the continuing education of Brazilian health professionals are emphasized.